Gal-3 (Galectin-3) and KCa3.1 Mediate Heterogeneous Cell Coupling and Myocardial Fibrogenesis Driven by βAR (β-Adrenoceptor) Activation. Issue 2 (February 2020) - She, Gang; Hou, Meng-Chen; Zhang, Yu; Zhang, Yi; Wang, Yan; Wang, Hui-Fang; Lai, Bao-Chang; Zhao, Wei-Bo; Du, Xiao-Jun; Deng, Xiu-Ling
Abstract : Heart failure is associated with sympatho-βAR (β-adrenoceptor) activation and cardiac fibrosis. Gal-3 (galectin-3) and KCa 3.1 channels that are upregulated in diverse cells of diseased heart are implicated in mediating myocardial inflammation and fibrosis. It remains unclear whether Gal-3 interacts with KCa 3.1 leading to cardiac fibrosis in the setting of βAR activation. We tested the effect of KCa 3.1 blocker TRAM-34 on cardiac fibrosis and inflammation in cardiac-restricted β2 -TG (β2 AR overexpressed transgenic) mice and determined KCa 3.1 expression in β2 -TG×Gal-3 −/− mouse hearts. Mechanisms of KCa 3.1 in mediating Gal-3 induced fibroblast activation were studied ex vivo. Expression of Gal-3 and KCa 3.1 was elevated in β2 -TG hearts. Gal-3 gene deletion in β2 -TG mice decreased KCa 3.1 expression in inflammatory cells but not in fibroblasts. Treatment of β2 -TG mice with TRAM-34 for 1 or 2 months significantly ameliorated cardiac inflammation and fibrosis and reduced Gal-3 level. In cultured fibroblasts, Gal-3 upregulated KCa 3.1 expression and channel currents with enhanced membrane potential and Ca 2+ entry through TRPV4 (transient receptor potential V4) and TRPC6 (transient receptor potential C6) channels leading to fibroblast activation. In conclusion, βAR stimulation promotes Gal-3 production that upregulates KCa 3.1 channels in noncardiomyocyte cells and activates KCa 3.1 channels in fibroblasts leading to hyperpolarization of membrane potential and Ca 2+ entry via TRP channels. Gal-3–KCa 3.1 signaling mobilizes diverse cells facilitating regional inflammation and fibroblast activation and hence myocardial fibrosis. Abstract : Supplemental Digital Content is available in the text.